Intraoperative consultation in gynecologic pathology - Škapa, Petr; Pluta, Marek (Ceskoslovenska patologie, 2018)
Intraoperative consultation represents an integral part of diagnostic protocols in gynecologic oncology. It may be indicated 1) to evaluate the biologic nature of a pathologic process (distinction between nonneoplastic lesions and tumors), 2) to classify the histologic type of tumor and assess its biologic behavior (typing), 3) to confirm or rule out the metastatic origin of a tumor, 4) to determine the degree of differentiation and extent of local spread of a malignant tumor (grading and staging), 5) to detect tumor deposits in lymph nodes, 6) to examine surgical resection margins, 7) to detect products of conception in uterine curettings when ectopic pregnancy is suspected and 8) to collect native tumor tissue for ancillary studies (molecular methods, flow cytometry). A frozen section of adnexal masses is commonly requested and focused primarily on the recognition of malignant tumors, the distinction between borderline tumors and carcinomas, and the identification of a metastatic process in the ovary. An intraoperative consultation may also be beneficial in the risk stratification of patients with endometrial carcinoma for the indication of lymphadenectomy, in the assessment of an endocervical surgical resection margin during fertility sparing and less radical surgery for the carcinoma of uterine cervix and in the detection of tumor spread into the lymph nodes (including sentinel lymph nodes). For the appropriate evaluation of a frozen section, awareness of the relevant clinical data and history of the patient, interpretation of the histologic findings in the context of macroscopic appearance of a specimen and an active interaction with the surgeon are required as essential conditions. Keywords: intraoperative consultation - frozen section - gynecologic pathology - tumors of ovary - metastases - sentinel lymph node.
Keywords: konziliární vyšetření a konzultace; Lymph Nodes; Referral and Consultation; Frozen Sections; zmrazené řezy; lymfatické uzliny; lidé; Female; Genital Neoplasms, Female; Pregnancy; staging nádorů; nádory ženských pohlavních orgánů; těhotenství; Neoplasm Staging; ženské pohlaví; Humans